Functional Double-Bundle Anterior Cruciate Ligament Reconstruction Through a Single Bone Tunnel Using Hamstring Tendon Autografts With Preserved Insertions - Yingguang Zhu, M.M.; Baofeng Zhao, M.M.; Wentao Xiong, M.M.; Fei Zhang, M.M.; Yuxin Xie, M.M.; Jipeng Ma, M.B.; Qiang Zhang, M.D., Ph.D. (Arthroscopy Techniques)
Existing anterior cruciate ligament (ACL) reconstructions mainly include anatomic single-bundle reconstruction and anatomic double-bundle reconstruction, and both methods have their advantages and disadvantages. The purpose of this article is to describe the functional double-bundle ACL reconstruction using hamstring tendon autografts with preserved insertions (i.e., the double-bundle approach through a single bone tunnel that better mimics the functional characteristics of the natural ACL).